Adhesive Bifidobacterium Induced Changes in Cecal Microbiome Alleviated Constipation in Mice - Wang, Linlin; Chen, Cailing; Cui, Shumao; Lee, Yuan-kun; Wang, Gang; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Frontiers in Microbiology, 2019)
Constipation, which seriously affects living quality of people, is a common gastrointestinal disease. The engagement of the intestinal flora in the development of symptoms of constipation has been frequently hypothesized. In this study, constipated mice induced by loperamide were used to investige the alleviation of constipation by bifidobacteria. Bifidobactria was sorted out according to their adhesive properties into two groups. One group combined multiple strains of Bifidobacterium with adhesion property (CMB1), the other combined multiple strains of Bifidobacterium without adhesion property (CMB2). It was found that CMB1 can alleviate constipation more efficiently by improving the water, proprionate and butyrate content in faeces, and overall gastrointestinal transit time. Meanwhile, from the perspective of faecal microbiota, CMB1 alleviated constipation mainly by increasing the relative abundances of genera (Bifidobacterium, Lactobacillus and Prevotella) associated with rapid bowel movement. From the perspective of cecal microbiota, CMB1 alleviated constipation mainly by increasing the relative abundances of genera Lactobacillus, Bacteroides, unclassified S24-7, Dorea, Ruminococcus, Coprococcus, and Rikenella, and decreasing the relative abundances of genera Oscillospira, Odoribacter and Unclassified F16, which are associated with methane production and colonic transit. Overall, changes of microbiota in caecum by CMB1 reflect the stage of constipation in mice more comprehensively than that in faeces.